Semantic Structure Verb ‘open’ in Indonesian and Japanese : Natural Semantic Metalanguage - Jaka Budiman; Mulyadi; Siti Muharami Malayu (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This study discusses the semantic structure of the verb 'open' in Indonesian and Japanese. This research uses the MSA theory pioneered by Wierzbicka. Data was obtained and collected using the interview method. The results of the findings obtained two categorizations of the verb 'open' in Indonesian and Japanese, they are: a) using tools (by using tools) and b) using hands (by part of body). The semantic structure of the verb 'open' in Indonesian and Japanese is almost similar. Even so, there are several different verbs in the semantic structure, including: meretas (é–‹å°ã™ã‚‹kaifÅ« suru), merintis & merambah (é–‹æ‹“ã™ã‚‹ kaitaku suru), mementang, membentangkan, membeber, menggelar & menghamparkan (åºƒã’ã‚‹hirogeru), dan menyingkap (æ²ã‚‹mekuru & ã¯ã ã‘ã‚‹hadakeru). The difference in the semantic structure of the Indonesian and the Japanese language occurs due to the cultural characteristics of the two peoples and the different language differences. Thus, it also results in a different mindset in each language.